Seismic Performance of Post-Northridge Welded Connections - Yilmaz, Orkun; Bekiroglu, Serkan (LATIN AMER J SOLIDS STRUCTURES, 2018)
Post-Northridge welded connections are widely used in engineering projects as lateral-force-resisting systems. In this study, we aim to assess the cyclic performance of the post-Northridge welded connections to compare the connections with each other. For this purpose, we focus on Welded Un-reinforced Flange - Welded Web (WUF-W), Welded Flange Plate (WFP) and Reduced Beam Section (RBS) connections. ANSYS Finite Element Analysis (FEA) software is used to do this investigation and evaluate the adequacy of the numerical analysis through an experimental specimen from the literature. Welded connections are designed according to ANSI 358-10 and FEMA-350 using the same material properties, beam spans, and steel profiles so on to make comparison possible. Material and geometry nonlinearities are adequately considered and also hexahedral solid elements are used in three-dimensional FEA. Based on the analyses subjected to cyclic loading, the performance of the connections are compared in terms of failure modes, plastic hinge locations, hysteretic curves, energy dissipation capacities, hysteretic equivalent viscous damping ratio and initial rotational stiffness values. The results showed that using WFP provides high stiffness in a connection while using RBS provides high safety in a connection.
Keywords: WUF-W connection; WFP connection; RBS connection; finite element simulation; nonlinear analysis; MOMENT CONNECTIONS; CYCLIC BEHAVIOR; LOCAL DETAILS; PANEL ZONE; I-BEAM; PLATE; Engineering; Mechanics